EFFECT OF MILK ON CHILDREN'S ORGANISMS - Damira Turdibekovna Atabayeva; Arzigul Ashirbayeva (European Science Publishing, 2024)
This article is written about the positive effect of cow's and goat's milk consumed in the morning breakfast on the children's body. The composition and beneficial properties of cow and goat milk are widely covered.
Keywords: milk, metabolism, health, immunity, blood circulation, calcium, vitamin, breakfast, organism.